Evaluation System for the Reading Al-Quran Private Program Using the Iqra Method - Larasati, Oktafiani; Mubarak, Fadhil; Riedha, Ali; Rahmati, Arinal; Setiawan, Eko (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This evaluation study aims to determine the quality and output of the Private Program for Reading Al-Quran using the Iqra Method to eliminate illiteracy in Reading Al-Quran for Santri at Dayah Ummul Ayman Aceh. The method used in descriptive quantitative research. The data taken is primary data. The data source comes from questionnaires filled out by research subjects. This research is evaluation research using the Quality Evaluation Model and Learning Output, better known as the EKOP Model. This research was conducted at the Private Program for Reading Al-Quran using the Iqra Method at Dayah Ummul Ayman, Putoh Village, Samalanga District, Bireuen Regency, Aceh Province in June 2023 with a sample of 45 santri (N = 45). Data collection using tests and questionnaires. Data were analyzed with descriptive statistical techniques using IBM SPSS Statistics 25 software. The results of the study found that the quality of learning in the private program of reading Al-Quran with the Iqra method at Dayah Ummul Ayman had gone well. However, Learning Facilities are still in the Adequate category. The Learning Output in the Private Program Reading Al-Quran with the Iqra Method at Dayah Ummul Ayman in terms of Academic Proficiency has achieved a fairly high score. However, the Learning Output on the Personal and Social Proficiency indicators is still in the Adequate category. The recommendations for improvement given are to improve learning facilities better. In addition, learning output in the context of personal skills and social skills must also be improved.